Sosialisasi Rogatory Sistem Bagi Calon Kenshushei Perikanan Sebagai Pekerja Migran Indonesia - Ria Wierma Putri; Yunita Maya Putri; Agus Triono; Melly Aida (Journal of Engineering and Information Technology for Community Service, 2022)
Indonesian Migrant Workers (PMI) are the country's largest foreign exchange earner. Often dubbed as foreign exchange heroes, it does not make them free from problems while working abroad. Often PMIs are victims of violence and other crimes, especially illegal PMIs. PMI's lack of understanding of the law is one of the factors causing the high number of legal cases experienced by PMI. The form of protection for Indonesian citizens who are abroad should be socialized to PMI Candidates. Kenshusei are basically apprentices stationed in Japan, one of the fields that sends kenshusei a lot is fisheries. For this reason, this activity aims to provide insight to PMIs regarding the rights and obligations as well as protection related to the Rogatory System. The Rogatory System is run by the Ministry of Foreign Affairs and the Supreme Court. The target of this service is PMI/PMI candidates to be able to understand the Rogatory System as a means of protection for PMIs working abroad. The methods used in this service are counseling and focus group discussions (FGD).